Pre-season Fitness Level and Injury Rate in Professional Soccer – A Prospective Study - Eliakim, Eyal; Doron, Ofer; Meckel, Yoav; Nemet, Dan; Eliakim, Alon (Sports Medicine International Open, 2018)
The aim of the present study was to assess prospectively the effect of pre-season fitness on injury rate during the competitive season among professional soccer players. Thirty-one players participated in the study during two consecutive competitive seasons (2015–16 and 2016–17; a squad of 22 players in each season). During the 6-week pre-season training period (8 training sessions and a friendly match every week, 14–18 training hours/week) there was a significant improvement in VO2 max, a significant increase in ideal and total sprint time and no change in vertical jump, flexibility and repeated sprint-test performance decrement. During the two consecutive seasons, 28 injuries were recorded. Ten injuries were classified as mild (missing 3–7 days of practice/match), 8 as moderate (missing 8–28 days) and 10 as severe (missing >28 days). The rate of match injuries was higher (9.4 per 1000 match hours) compared to practice injuries (4.7 per 1000 training hours). Most injuries were overuse injuries (72%) of the lower limbs (71%). Most of match injuries occurred during the last 15 min of each half. There were no differences in fitness characteristics in the beginning of pre-season training between injured and non-injured players. However, improvements in VO2 max during the pre-season training period were significantly lower among injured players (0.9±5.5%) compared to non-injured players (10.4±6.5%, p<0.05). Our results emphasize the importance of pre-season training in professional soccer players not only for improvement in fitness but also for injury prevention during the following competitive season.
Keywords: physical conditioning; prevention; football; musculoskeletal injuries